Eocene-Oligocene southwest Pacific Ocean paleoceanography new insights from foraminifera chemistry (DSDP site 277, Campbell Plateau) - Hodel, F.; Fériot, C.; Dera, G.; De Rafélis, M.; Lezin, C.; Nardin, E.; Rouby, D.; Aretz, M.; Antonio, P.; Buatier, M.; Steinmann, M.; Lacan, F.; et al. (Frontiers in Earth Science, 2022)
Despite its major role in the Earth's climate regulation, the evolution of high-latitude ocean dynamics through geological time remains unclear. Around Antarctica, changes in the Southern Ocean (SO) circulation are inferred to be responsible for cooling from the late Eocene and glaciation in the early Oligocene. Here, we present a geochemical study of foraminifera from DSDP Site 277 (Campbell Plateau), to better constrain thermal and redox evolution of the high latitude southwest Pacific Ocean during this time interval. From 56 to 48 Ma, Mg/Ca- and δ18O-paleothermometers indicate high surface and bottom water temperatures (24-26 °C and 12-14 °C, respectively), while weak negative Ce anomalies indicate poorly oxygenated bottom waters. This is followed by a cooling of ~4° between 48 and 42 Ma, possibly resulting from a weakening of a proto-EAC (East Australian Current) and concomitant strengthening of a proto-Ross gyre. This paleoceanographic change is associated with better ventilation at Site 277, recorded by an increasing negative Ce anomaly. Once this proto-Ross gyre was fully active, increasing biogenic sedimentation rates and decreasing Subbotina sp. δ13C values indicate enhanced productivity. This resulted in a shoaling of the oxygen penetration in the sediment pile recorded by increasing the foraminiferal U/Ca ratio. The negative Ce anomaly sharply increased two times at ~35 and ~31 Ma, indicating enhanced seawater ventilation synchronously with the opening of the Tasmanian and Drake Passage gateways, respectively. The Oligocene glaciation is recorded by a major increase of bottom seawater δ18O during the EOT (Eocene-Oligocene Transition) while Mg/Ca-temperatures remain rather constant. This indicates a significant ice control on the δ18O record.